Modified cassava starch production a plant design - Cruz, Ruby Bernadette C. (College of Engineering, 1992)
Products: Acid modified, oxidized modified starch, cross-linked starch, instant starch -- Plant site: Guimaras, Iloilo -- Plant capacity: 902 MT/year -- Gross sales: P 24,046,510 -- Net profit: P 8,058,583 -- Total capital investment: P 14,095,000 -- Total production cost: P 11,648,690 -- Payback period (after tax): 1.75 years -- Return on investment (after tax): 57.17% -- Break-even capacity: 2.18%